2021
DOI: 10.1002/cbic.202000876
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Multiple, Nonproteogenic Substitutions to Optimize CSP:ComD Hydrophobic Interactions in Group 1 Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae (pneumococcus) is a human pathobiont that causes drastic antibiotic‐resistant infections and is responsible for millions of deaths universally. Pneumococcus pathogenicity relies on the competence‐stimulating peptide (CSP)‐mediated quorum‐sensing (QS) pathway that controls competence development for genetic transformation and, consequently, the spread of antibiotic resistance and virulence genes. Modulation of QS in S. pneumoniae can therefore be used to enervate pneumococcal infectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We advanced these results by incorporating multiple mutations containing several of the nonproteogenic amino acids in the CSP1 sequence. 33 The findings from this study provided several important structural insights, specifically the preference of ComD1 for linear, hydrophobic, nonproteogenic amino acids. Combined, the results obtained from these two studies revealed strong potential for even further optimization of the binding interaction between CSP1 and ComD1.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We advanced these results by incorporating multiple mutations containing several of the nonproteogenic amino acids in the CSP1 sequence. 33 The findings from this study provided several important structural insights, specifically the preference of ComD1 for linear, hydrophobic, nonproteogenic amino acids. Combined, the results obtained from these two studies revealed strong potential for even further optimization of the binding interaction between CSP1 and ComD1.…”
Section: Introductionmentioning
confidence: 80%
“…In the context of S. pneumoniae CSP1, our previous investigations of the CSP1-ComD1 binding interaction revealed that positions 4, 7, 8, 11, and 12 in CSP1 have unoccupied space within the receptor binding site. 32,33 We aimed to assess the steric limit of the CSP1-ComD1 interaction by utilizing bulkier, hydrophobic nonproteogenic substituents. To this end, aliphatic and aromatic hydrophobic residues (Leu, Ile or Phe) in positions 4, 7, 8, 11, and 12 were substituted with the nonproteogenic amino acids, cyclohexylalanine (Cha) or homoleucine (HLeu) (Fig.…”
Section: Design and Synthesis Of Nonproteogenic Csp1 Analogsmentioning
confidence: 99%
“…Excitingly, HSGN-94 showed high efficacy in diminishing the burden of MRSA in a murine skin infection model and also reduced the pro-inflammatory cytokines in MRSA-infected wounds. Antimicrobial resistance is a growing threat, and many groups have disclosed new chemical scaffolds that inhibit bacterial growth. Detailed mechanistic work to uncover how each of these unique compounds kill bacteria would likely reveal many novel tactics to tackle this global health challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up studies have focused on optimizing the degree of occupancy of the CSP1 binding pockets within the ComD1 receptor by utilizing conservative substitutions at these key hydrophobic residues of CSP1. [ 92–94 ] Through the incorporation of bulkier, hydrophobic nonproteogenic amino acids, Milly et al were able to develop pneumococcal QS modulators with high potency and superior metabolic stability, while remaining nontoxic against mammalian cells. [ 94 ]…”
Section: Peptide‐based Qs Systems As Therapeutic Targetsmentioning
confidence: 99%
“…Follow-up studies have focused on optimizing the degree of occupancy of the CSP1 binding pockets within the ComD1 receptor by utilizing conservative substitutions at these key hydrophobic residues of CSP1. [92][93][94] Through the incorporation of bulkier, hydrophobic nonproteogenic amino acids, Milly et al were able to develop pneumococcal QS modulators with high potency and superior metabolic stability, while remaining nontoxic against mammalian cells. [94] The first position on the pherotype 1 AIP (CSP1, Table 1; with its unique primary structure, each CSP represents a separate pheromone type-pherotype) was found to be necessary for competence development, as Glu1 to Ala mutation (to afford CSP1-E1A) was sufficient to convert the signaling peptide into a competitive inhibitor capable of inhibiting competence induction and regulation of down-stream genes in S. pneumoniae.…”
Section: Com Qs System As Therapeutic Targetmentioning
confidence: 99%